Detection of low molecular weight compounds using carbon nanotube grafted resonators - Swarnalatha, B. (2013)
A biosensor platform based on single walled carbon nanotube (SWCNT) grafted quartz resonator is reported in this study. The generated SWCNT network on the resonator electrode is used to enhance the surface area for receptor immobilization and thereby the sensitivity. This approach enables detection of low molecular weight compounds in a direct assay format. Micro-gravimetric detection of two potentially harmful herbicides, atrazine and 2,4-dichlorophenoxyacetic acid (2,4-D) demonstrates the enhanced sensing capabilities of the developed biosensor platform. Antibodies raised against the herbicides are covalently attached to the SWCNTs, which are tethered on to the resonator electrodes via cysteine linkers. Imaging surface plasmon resonance and polarization modulation infrared reflection absorption spectroscopy are used to characterize the sensing surface and the covalent immobilization of the antibodies. The experimental results reveal that grafting SWCNT on resonator electrodes improves the sensing performance, as compared to a planar architecture, thereby enabling direct detection of atrazine and 2,4-D at analytically relevant concentration levels.